The chitin-glucan complex of Saccharomyces cerevisiae. III. Electron-microscopic study of the prebudding stage - Seichertová, O; Beran, K; Holan, Z; Pokorný, V (Folia microbiologica, 1975)
Differentiation of the cell wall of Saccharomyces cerevisiae at the site of the future bud was followed. A lentil-like structure originates on the inner side of the cell wall during the first phase. At the same time, an electron-dense layer occurs at the boundary between the inner layer of the cell wall and the lentil-like structure. During the second phase granular material is accumulated at the lower side of the lentil-like structure. During the third phase the lentil-like structure is split apart due to proliferation of the granular material resulting in formation of the base of the encircling region. The marked electron-dense layer observed from the first phase is attached to the surface of the encircling region during differentiation of the latter. During the budding proper the outer layers of the cell wall protrude and the end of the encircling region, together with the adjacent electron-dense layer, acquire their definitive appearance of rings, observed as marked electron-transparent and electron-dense tears on ultrathin sections.
Keywords: buněčné dělení; kyselina chlorovodíková; Models, Biological; Cell Wall; hydrolýza; Time Factors; buněčná stěna; časové faktory; polysacharidy; chitin; Chitin; Hydrolysis; Cell Division; biologické modely; Saccharomyces cerevisiae; Hydrochloric Acid; Polysaccharides